2015
DOI: 10.1111/vox.12280
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐operative cell salvage in cardiac surgery may increase platelet transfusion requirements: a cohort study

Abstract: The CS use increases platelet requirements and has no impact on the rate of RBC transfusion in our population. These findings warrant caution with generalized use and require larger studies to confirm its results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…This may explain the potential increase in the risk of FFP transfusion in the CS group. In a large study of over 600 patients from our centre , we found that the use of CS increases the rate of platelet and FFP transfusion consistent with the hypothesis of activated haemostasis in shed or CPB blood.…”
Section: Discussionsupporting
confidence: 76%
“…This may explain the potential increase in the risk of FFP transfusion in the CS group. In a large study of over 600 patients from our centre , we found that the use of CS increases the rate of platelet and FFP transfusion consistent with the hypothesis of activated haemostasis in shed or CPB blood.…”
Section: Discussionsupporting
confidence: 76%
“…The use of cardiac bypass is known to cause extended bleeding times and is associated with increased post‐operative haemorrhage in patients with normal peripheral blood platelet counts. Hypothermia and heparin treatment are strongly inhibitory on platelet aggregation , and intraoperative cell salvage may cause acute platelet depletion . Moreover, the increasingly frequent use of aspirin and P2Y 12 inhibitors, such as clopidogrel, prasugrel and ticagrelor in acute coronary syndromes , often results in severe platelet inhibition during cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, existen datos que declaran que la reinfusión de glóbulos rojos procedente del RC sin plaquetas, plasma, ni factores de coagulación, mitiga efectos negativos de la función hematológica del paciente, lo que justifica que en estos pacientes tengan una necesidad transfusional, sobre todo al consumo de factores de coagulación 25 , ya que provoca una sensibilización plaquetaria significativa, pero insistimos que no establecen un marco comparativo con aquellos pacientes que recibieron la transfusión sanguínea, por tanto coincidimos con otros estudios que postulan que toda investigación que se encauce en el uso de los recuperadores celulares como medida a la transfusión sanguínea, merecen precaución en cuanto su utilización de forma generalizada, por lo que requieren estudios más amplios para confirmar sus resultados 26 .…”
Section: Discussionunclassified